2021
DOI: 10.3390/jmse9121366
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation of Multiscale Vortices in Circular Cylinder Wake at Re = 9500

Abstract: Cavitation characteristics in the wake of a circular cylinder, which contains multiscale vortices, are numerically investigated via Large Eddy Simulation (LES) in this paper. The Reynolds number is 9500 based on the inlet velocity, the cylinder diameter and the kinematic viscosity of the noncavitation liquid. The Schneer–Sauer (SS) model is applied to cavitation simulation because it is more sensitive to vapor–liquid two-phase volume fraction than the Zwart–Gerber–Belamri (ZGB) model, according to theoretical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…The convergence standard of all residuals is 10 -6 . The validation of the present numerical simulation can be found in our previous work (Gu et al, 2021). It should be mentioned that in the following analyses, all parameters shown in the figures are nondimensionalized via the cylinder diameter and the inlet velocity.…”
Section: Numerical Setupmentioning
confidence: 69%
“…The convergence standard of all residuals is 10 -6 . The validation of the present numerical simulation can be found in our previous work (Gu et al, 2021). It should be mentioned that in the following analyses, all parameters shown in the figures are nondimensionalized via the cylinder diameter and the inlet velocity.…”
Section: Numerical Setupmentioning
confidence: 69%
“…The convergence criterion of all residuals is 10 -6 . The validation of the present numerical simulation can be found in our previous work (Gu et al, 2021). It should be mentioned that in the following analyses, all parameters shown in the figures are nondimensionalized via the cylinder diameter and the inlet velocity.…”
Section: Numerical Setupmentioning
confidence: 69%
“…In addition, He indicated that the cavitation inception formed on the cylinder can depend on the effects of the Reynolds number. Gu et al [10] numerically studied the cavitation dynamics and multiscale vortices formed behind a circular cylinder using the large eddy simulation (LES) method at a middle Reynolds number of about 9500. Brandao et al [11] investigated the cavitation behavior behind a circular cylinder at different cavitating regimes.…”
Section: Introductionmentioning
confidence: 99%